Intertextual narrative? The perception of coldwater cure by patients of Vincenz Priessnitz - Hanulík, Vladan (Theatrum historiae, 2013)
Paper is aimed on comparison of different types of text narratives relating to hydropathy, coldwater cure and its founder Vincenz Priessnitz. Objective of comparison is the effort to determine extent or even the very potentiality of influence of textual corpuses on the individual perception of medical therapy in spa Gräfenberg from the patient’s point of view and the creation of unique metanarrative of hydropathical discourse in the third decade of 19th century. The analytical frame is based upon the theoretical concept of post structural linguistic analysis of Roland Barthes and process model of perception of Eugene T. Gendlin.